'The Market is Far Away'. Global Connections and Economic Remoteness in Rural Ukraine. Issue 3 (16th March 2021) - Kaneff, Deema
Abstract: This article examines the role of the 'global market' in the exacerbation of economic remoteness in rural Ukraine. Based on a case study of a UK-sponsored project that set up a sewing centre in a rural community in Odesa province, I explore how unequal access to the global economy is determined by the type of market sought and the type of product designated for production. The approach looks critically at 'the market'—as both a Western-oriented ideological construct and set of practices—that serves to distance the community from centres of global economic importance, both in a temporal and spatial sense.